ALTERNATIF DESAIN STRUKTUR GEDUNG UNIVERSITAS MUHAMMADIYAH LAMONGAN MENGGUNAKAN DUAL SYSTEM EBF TAHAN GEMPA - Ahmad Athoillah Syaichul Ghulam; Bantot Sutriono (Jurnal Taguchi : Jurnal Ilmiah Teknik dan Manajemen Industri, 2023)
In this study, an alternative design of Universitas Muhammadiyah Lamongan was carried out using an earthquake-resistant steel structure with a dual system eccentrically braced frame. The existing design of Universitas Muhammadiyah Lamongan uses a concrete structure with a shearwall structural system. Steel structure is chosen as an alternative design because steel material has better ductility and lower weight than concrete, which is good for earthquake resistant buildings. Universitas Muhammadiyah Lamongan will be designed with a moment-resisting frame structure system in accordance with the provisions of SNI 1726: 2019 on earthquake resistant structure planning, SNI 1729: 2020 concerning building steel structures, SNI 7860: 2020 concerning earthquake-resistant steel structures and SNI 7972: 2020 concerning special moment-bearing steel structure connections. From the design results, the dimensions of the steel cross-section profiles used as beams are WF 500.200, WF 450.200, WF 400.200, WF 396.198, and WF 350.175. Meanwhile, the cross-sectional column profiles are KC 800.300, K700.300, K588.300, K600.200, and K500.200